Perancangan tas yoga modular untuk mengoptimalkan fungsi bagi yogi modern - Revana, Azzahra Haliza; Azhar, Hanif (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
The increasing trend of yoga in recent years has been driven by growing awareness of its physical and mental benefits. Yoga requires specific equipment such as mats, yoga straps, water bottles, and other personal items. However, interviews indicate that the yoga bags currently used by practitioners are not yet optimal, particularly in accommodating these necessities and providing flexibility for use in both studio and outdoor yoga classes. This study aims to design a yoga bag that prioritizes functionality and comfort through a modular system that enhances user flexibility in various yoga settings. A qualitative research approach was employed, utilizing observations and interviews to analyze user needs and lifestyles, while the design process was conducted using the Double Diamond Model developed by the Design Council. This study is expected to result in a functional and well-organized yoga bag design that effectively meets the needs of yoga practitioners in carrying their equipment efficiently.